Remote Home - A Universal Control for Residential Environments - Kronbauer, Artur Henrique; Araujo, Brunno Brito; Gomes, Fabio Fonseca B. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2015)
Currently, several advances are taking place in the area of residential environments, providing convenience and pleasure to different profiles of people. With the increased use of smartphones, people will be able to use them to control their existing home appliances. In this scenario, we propose a platform structured into three layers: (i) Interaction, using a mobile application with the function of a universal remote; (ii) Connectivity, middleware responsible for managing the communication between the Interaction Layer and the Actuator Layer; and (iii) Actuators, microprocessors connected to home appliances so that they can be controlled. Some tests were conducted to validate the platform and identify its potential. The preliminary results indicated that the platform functions properly and efficiently.